Feasibility Analysis of Yogyakarta-Bawen Tollway from Economic and Financial Aspect - Abdillah, Zulfan Akbar; Kartika, Anak Agung Gde (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Tollway is public roads that are part of the road network system and as national roads whose users are required to pay tolls. The implementation of tollway aims to increase the efficiency of distribution services in order to support increasing economic growth, especially in areas that have a high level of development. Central Java is an area that has high potential of tourism. One of those is Borobudur Temple. To increase this potential, a good road network is needed, one of which is the construction of the Yogyakarta-Bawen Tollway. The construction of the Yogyakarta-Bawen Tollway is expected to have great benefits, especially the connectivity of the Trans Java tollway which is supported by the Government. The project feasibility study is aimed to assess the carried-out project. The meaning of the assessment here is providing a recommendation whether the project is feasible to be carried out or should be postponed. In carrying out this feasibility study, various aspects will be involved to decide the feasibility of a project. The economic and financial aspects are aspects that need to be considered in the implementation of a project feasibility study. By carrying out this study, the amount of savings from VOC (Vehicle Operating Costs) and the time value when this tollway is operated, so that later on, it will be known, whether the construction of this tollway is feasible from the economic and financial perspective. The analysis results of the economic feasibility showed that the BCR value was 4.102 (BCR>1), the NPV was Rp8.824.453.255.243 (NPV> 0), while in the financial feasibility analysis showed the BCR value was 2.767 (BCR>1), NPV was Rp45.719.816.667.039, IRR of 11.24% (IRR>Interest rates), and Payback Period in the 18th year, 10th month, 21st day after the tollway is operated. Based on this analysis, it can be concluded that the Yogyakarta-Bawen Tollway is feasible from an economic and financial aspect.